New frontiers in the philosophy of intellectual property - Lever,Annabelle,Ed (Cambridge intellectual property and information law, 2012)
"Are intellectual property rights a threat to autonomy, global justice, indigenous rights, access to lifesaving knowledge and medicines? The essays in this volume examine the justification of patents, copyrights and trademarks in light of the political and moral controversy over TRIPS (the Agreement on Trade-Related Aspects of Intellectual Property Rights). Written by a distinguished international group of experts, this book draws on the latest philosophical work on autonomy, equality, property ownership and human rights in order to explore the moral, political and economic implications of property rights in ideas. Written with an interdisciplinary audience in mind, these essays introduce readers to the latest debates in the philosophy of intellectual property, whether their interests are in the restrictions that copyright places on the reproduction of music and printed words or in the morality and legality of patenting human genes, essential medicines or traditional knowledge"--